Composites hydrogels with enhanced solid foam formation. (November 2022) - Zhang, Zhen; Lucia, Lucian; Abidi, Noureddine
Abstract: It is discovered that sustainable polymers including gelatin and soy protein polymer assist the transformation of poly (vinyl alcohol) (PVOH) hydrogel into solid foams via freeze-drying process; while freeze-dry neat PVOH hydrogels give rise to solid foams with wrinkle patterns and shrinkage. Simultaneous improvement in the thermal stability was also achieved. The mechanisms for the improved performance were also preliminarily proposed. Graphical abstract: Image 1 Highlights: Soy protein polymer and gelatin helped hydrogel form a solid foam. A simultaneous improved thermal stability was accompanied. The mechanism for the improvement was preliminarily proposed.